Determination of pentachlorophenol in drinking water - Gaspar, I. F. [UNESP]; Polese, L. [UNESP]; Minelli, E. V. [UNESP]; Ribeiro, M. L. [UNESP]; Jardim, E. F G [UNESP] (FapUNIFESP (SciELO), 1997)
In this study, an in situ derivatization and extraction method for the determination of pentachlorophenol (PCP) has been applied successfully in the analysis of water samples. The PCP derivative analysis was performed by gas-liquid chromatography with electron capture detection. The limit of detection of the method is 1 μg/L and recoveries averaged 78-108% for PCP acetate at levels of 2, 10 and 20 μg/L.
Keywords: Gas chromatography; In-situ derivatization; Pentachlorophenol; Water